Effectiveness of Purple Sweet Potato Extract and Disclosing Substance for Plaque Identification - Yenti, Aflinda; Sukanti, Eka; Damhuji; Ayatullah, M. Ibraar (JURNAL INFO KESEHATAN, 2022)
Oral hygiene is an indicator of oral and dental health which can be assessed based on the presence or absence of organic deposits, such as pellicle, materia alba (dental deposit), food residue, calculus, and dental plaque. Plaque is the cause of tooth decay among the world's population. Plaque on the tooth surface can be used as an indicator of oral hygiene. Poor cleaning can lead to stickier plaque and tartar after calcification. The thin plaque is almost the same as the color of the teeth, so that plaque cannot be seen with the naked eye. The presence of plaque that is formed from contact with oral fluids can be detected by using certain dye. This study aims to determine the Effectiveness of Purple Sweet Potato Extract and Disclosing substance for Plaque Identification among the children in Aisyah Orphanage, Tilatang Kamang Sub-District, Agam District. This was a quasi-experimental study with a post-test-only design. The samples of this study were 30 children at Aisyah Orphanage, Tilatang Kamang Sub-District, Agam District, with the inclusion criteria of children with permanent teeth and index teeth. The samples were selected through total sampling technique. The results showed that after applying purple sweet potato extract to the children at Aisyah Orphanage in Bukittinggi City, most of them had the Patient Hygiene Performance index (PHP) in the moderate criteria (50%). Furthermore, after applying disclosing substances to the children at Aisyah Orphanage in Bukittinggi City, most of them had the PHP index in the poor criteria (56.7%). The t-test independent statistical test results obtained a p-value of 0.000 (p <0.005), indicating a significant difference between sweet potato extract and disclosing substance. Disclosing substance was more effective than purple sweet potato extract in identifying plaque on the tooth surface. Further study is recommended to apply purple sweet potato extract with different concentrations as an alternative ingredient to identify plaque on the tooth surface.